2000
DOI: 10.1136/bmj.321.7273.1371
|View full text |Cite
|
Sign up to set email alerts
|

Atypical antipsychotics in the treatment of schizophrenia: systematic overview and meta-regression analysis

Abstract: Objective To develop an evidence base for recommendations on the use of atypical antipsychotics for patients with schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
499
7
30

Year Published

2002
2002
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 954 publications
(567 citation statements)
references
References 16 publications
31
499
7
30
Order By: Relevance
“…Moreover, the neurological scale scores (SAS, AIMS and BAS) were low at baseline and did not increase during the study, thus indicating that neither drug induced a significant level of extrapyramidal symptoms. These findings are consistent with those from previous studies showing that the atypical antipsychotics are associated with a lower incidence of extrapyramidal symptoms than the typical neuroleptics (Geddes et al 2000). In addition, both drugs produced low incidences of other adverse events, as indicated by the relatively small numbers of patients that withdrew from treatment for this reason.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, the neurological scale scores (SAS, AIMS and BAS) were low at baseline and did not increase during the study, thus indicating that neither drug induced a significant level of extrapyramidal symptoms. These findings are consistent with those from previous studies showing that the atypical antipsychotics are associated with a lower incidence of extrapyramidal symptoms than the typical neuroleptics (Geddes et al 2000). In addition, both drugs produced low incidences of other adverse events, as indicated by the relatively small numbers of patients that withdrew from treatment for this reason.…”
Section: Discussionsupporting
confidence: 92%
“…It also possesses some short-acting norepinephrine receptor antagonist activity, as well as some antihistaminergic activity (Leysen et al 1988;Janssen et al 1988). Studies have shown that it is at least as effective as the typical neuroleptics in patients with acute and chronic schizophrenia with positive and/or negative symptoms (Chouinard et al 1993;Hoyberg et al 1993;Marder and Meibach 1994;Carman et al 1995;Huttunen et al 1995;Peuskens and the Risperidone Study Group 1995) and that it is better tolerated than typical neuroleptics in terms of extrapyramidal side effects (Geddes et al 2000).…”
mentioning
confidence: 99%
“…These advantages observed in some, but not all, studies include improvement in measures of negative symptoms, cognitive test performance, depression, adherence, time to relapse, aggression, and suicide. A few studies using low doses of first-generation antipsychotic drugs, and recent head-to-head comparisons with public sponsorship in the United States and United Kingdom fail to support the superiority of second generation drugs (Jones et al, 2006, Lieberman et al, 2003aGeddes et al, 2005;Schooler et al, 2005;Lieberman, 2007). Some second-generation antipsychotic drugs cause very substantial adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…Several meta-analyses of RCTs have shown that atypical antipsychotics are less likely to cause EPS than conventional agents (Bagnall et al, 2003;Geddes et al, 2000). The EPS advantage of the atypical antipsychotics was the major reason why the National Institute of Clinical Excellence (NICE) Schizophrenia Guideline in the UK recommended that atypical antipsychotics should be first line drugs in the treatment of those with newly diagnosed schizophrenia and that patients treated with conventional antipsychotics who have unacceptable EPS should be switched to an atypical agent (National Institute for Clinical Excellence, 2002).…”
Section: Differential Risk Of Eps Among Antipsychotic Drugsmentioning
confidence: 99%